Resin composition, metal foil-clad laminated board and application of metal foil-clad laminated board
By sintering and crushing the modified boron nitride particles twice and combining them with the resin material, the problem of boron nitride cannot be filled in large quantities is solved, and the resin composition with high thermal conductivity and high peel strength is achieved, which improves the thermal conductivity and reliability performance of the metal-covered foil laminate.
Patent Information
- Application Number
- CN202411948086.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-27
AI Technical Summary
In the prior art, boron nitride cannot be filled in large quantities in the resin due to the sheet-like structure, resulting in limited improvement in thermal conductivity. At the same time, the increase in the amount of thermal conductivity will affect the adhesion and reduce the heat resistance and voltage resistance of the copper clad plate.
By mixing boron nitride with a sintering aid, performing two high-temperature sintering and crushing, modifying boron nitride particles are prepared and combined with a resin material, and a resin composition is designed to improve its filling rate and thermal conductivity in the resin.
The resin composition has high thermal conductivity and high peel strength and excellent bonding properties, so that the metal-covered foil laminate has excellent comprehensive performance in terms of high thermal conductivity and high reliability.
Smart Images

Figure BDA0005214192670000151 
Figure BDA0005214192670000161 
Figure BDA0005214192670000171
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of copper-clad laminates, and in particular relates to a resin composition, a metal foil-clad laminate and applications thereof. Background Art
[0002] With the rapid development of electronic products, the power consumption of electronic components is increasing, and the heat generated per unit area during working time is also increasing. In order to ensure the working stability of electronic components, higher heat dissipation performance requirements are also put forward for the boards used to construct the devices. If the heat dissipation of the board is not good, the reliability of the whole machine will be reduced, which will lead to product failure and shorten the service life of electronic products.
[0003] The core idea of solving the heat dissipation performance of the board in the industry is to design a dielectric layer and copper-clad laminate with high thermal conductivity. Introducing high thermal conductivity materials in the preparation of dielectric layers and copper-clad laminates is the main means to improve thermal conductivity. Since the cost of resins with good thermal conductivity is relatively high, adding thermal conductive fillers is currently a common practice. For example, CN115556439A discloses a high thermal conductivity polytetrafluoroethylene high-frequency copper-clad laminate, which is prepared by laminating a dielectric layer and a copper foil and pressing at high temperature. The raw materials for preparing the dielectric layer include: 10-20% fluorine resin emulsion, 3-6% silane coupling agent, 2-7% fiber reinforcement material, and the rest are thermal conductive fillers; the thermal conductive fillers include 10-30% layered boron nitride, 20-35% silicon powder, 10-15% aluminum nitride and 10-35% spherical aluminum oxide. CN110370750A discloses a high thermal conductivity copper clad laminate, comprising a core thermal conductive adhesive sheet and a surface thermal conductive adhesive sheet, wherein the core thermal conductive composition for preparing the core thermal conductive adhesive sheet comprises: 10-35 parts of bisphenol A epoxy resin, 5-10 parts of curing agent, 50-80 parts of filler, and 10-30 flame retardant; the surface thermal conductive composition for preparing the surface thermal conductive adhesive sheet comprises: 10-35 parts of surface epoxy resin, 5-10 parts of curing agent, 30-50 parts of filler, and 10-30 parts of flame retardant; the filler in the core material and the surface is a mixture of aluminum oxide and boron oxide in a mass ratio of 1:1. CN101767481A discloses a high thermal conductivity copper clad laminate, and its preparation method comprises the following steps: by weight, 60-90% of multifunctional epoxy resin is mixed with 10-40% of polyurethane to prepare a resin glue solution with a solid content of 60-90%; using dicyandiamide as a curing agent and 2-methylimidazole as an accelerator to prepare the resin glue solution into a glue solution with a gel time of 150-450s; and using a mixed filler of 40-60% of aluminum nitride and 40-60% of aluminum oxide as a filler of the glue solution; using the glue solution to impregnate glass cloth to prepare a bonding sheet, stacking a plurality of bonding sheets and coating them with copper foil, and hot pressing to form a high thermal conductivity copper clad laminate.
[0004] The thermal conductive fillers currently used in copper clad laminates include aluminum oxide, aluminum nitride, boron nitride, boron oxide, silicon powder, etc. Among them, the thermal conductivity of boron nitride is particularly outstanding, and it has great application potential in thermal conductive materials. However, boron nitride has a lamellar structure and a large specific surface area, so it cannot be filled in large quantities in the resin, which greatly weakens the ability of boron nitride to improve the thermal conductivity of composite materials. Moreover, the increase in the amount of thermal conductive filler will also lead to the deterioration of the adhesion between the glue layer and the copper foil and the metal substrate, thereby weakening the heat resistance and voltage resistance of the copper clad laminate, resulting in poor reliability.
[0005] Therefore, developing a thermally conductive composite material with both high thermal conductivity and excellent adhesion is an urgent problem to be solved in the art. Summary of the invention
[0006] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a resin composition, a metal foil-clad laminate and applications thereof. By designing a preparation method, modified boron nitride particles with high thermal conductivity and high filling rate are obtained, so that the resin composition containing the modified boron nitride particles can achieve high thermal conductivity while also having high peel strength and excellent bonding properties, thereby enabling the metal foil-clad laminate to achieve excellent comprehensive performance in terms of high thermal conductivity and high reliability.
[0007] To achieve this object, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a resin composition, comprising a combination of a resin material and modified boron nitride particles.
[0009] The modified boron nitride particles are prepared by the following method, which includes: mixing boron nitride and a sintering aid, performing a first sintering and a first crushing to obtain primary particles; and performing a second sintering and a second crushing on the primary particles to obtain the modified boron nitride particles.
[0010] The sintering aid includes any one of calcium oxide, magnesium oxide, silicon oxide, yttrium oxide, niobium oxide, and potassium feldspar, or a combination of at least two thereof; based on the total mass of the boron nitride and the sintering aid being 100%, the mass of the sintering aid is 1-10%.
[0011] The present invention subjects boron nitride and a specific type of sintering aid to a first high-temperature sintering and crushing to obtain primary particles, and then subjects the primary particles to a second high-temperature sintering and crushing to obtain the modified boron nitride particles. Through the synergistic effect of the sintering aid and the two sinterings, the filling ratio of the modified boron nitride particles in the resin material can be increased, so that the resin composition has high thermal conductivity and high peel strength, excellent bonding performance, and effectively improves the comprehensive effect of the metal foil-clad laminate in terms of heat dissipation and reliability.
[0012] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the objectives and beneficial effects of the present invention can be better achieved and realized.
[0013] Preferably, the boron nitride includes any one of hexagonal boron nitride and cubic boron nitride, or a combination of at least two of them, and hexagonal boron nitride is further preferred.
[0014] Preferably, the average particle size of the modified boron nitride particles is 0.1-30 μm, for example, it can be 0.2 μm, 0.5 μm, 1 μm, 2 μm, 5 μm, 8 μm, 10 μm, 12 μm, 15 μm, 18 μm, 20 μm, 22 μm, 25 μm or 28 μm, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0015] In the present invention, the average particle size can be understood as D 50 Particle size, relevant data of particle size can be obtained by testing using MS3000 Malvern laser particle size analyzer.
[0016] In the present invention, the mass content of the modified boron nitride particles in the resin composition can be adjusted according to the requirements of the thermal conductivity, processability, peel strength, reliability and other properties of the material, and can be 10-92%, more preferably 20-92%.
[0017] Preferably, the mass percentage of the modified boron nitride particles in the resin composition is 30-92%, for example, it can be 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85% or 90%, and specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range, and 50-90% is further preferred.
[0018] As a preferred technical solution of the present invention, the mass percentage of the modified boron nitride particles in the resin composition is 30-92%, and more preferably 50-90%, so that the resin composition and the metal foil laminate prepared therefrom have high thermal conductivity, high peel strength and excellent reliability. If the content of the modified boron nitride particles is too low, the thermal conductivity of the resin composition and the plate will be reduced; if the content of the modified boron nitride particles is too high, the processability of the resin composition will be poor, and it will be difficult to prepare a qualified copper clad laminate.
[0019] In the present invention, taking the total mass of the boron nitride and the sintering aid as 100%, the mass of the sintering aid is 1-10%, for example, it can be 2%, 3%, 4%, 5%, 6%, 7%, 8% or 9%, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0020] The present invention mixes a specific type and amount of sintering aid with boron nitride, performs high-temperature sintering and crushing twice, and obtains specific modified boron nitride particles, which effectively solves the problem that lamellar boron nitride cannot be filled in large quantities, resulting in insufficient thermal conductivity of the material. The modified boron nitride particles have excellent thermal conductivity and a high filling rate in the resin material, so that the boron resin composition containing it has both high thermal conductivity and high peel strength. If the amount of the sintering aid is less than 1%, it is difficult to effectively modify the boron nitride and the filling ratio of boron nitride in the resin cannot be increased; if the amount of the sintering aid is greater than 10%, the thermal conductivity of the modified boron nitride and the resin composition containing it will be reduced.
[0021] Preferably, the mixed raw material further comprises other metal oxides, and the “other metal oxides” refer to metal oxides other than the sintering aid.
[0022] Preferably, the other metal oxides include aluminum oxide and / or beryllium oxide.
[0023] Preferably, taking the total mass of the boron nitride, sintering aids and other metal oxides as 100%, the mass of the other metal oxides is 1-10%, for example, it can be 2%, 3%, 4%, 5%, 6%, 7%, 8% or 9%, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0024] Preferably, the mixing method comprises physical dry mixing.
[0025] Preferably, the mixing time is 0.1-3h, for example, it can be 0.2h, 0.4h, 0.5h, 0.8h, 1h, 1.2h, 1.5h, 1.8h, 2h, 2.2h, 2.5h or 2.8h, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0026] Preferably, the first sintering is performed in an inert atmosphere.
[0027] Preferably, the inert atmosphere includes a nitrogen atmosphere and / or an argon atmosphere.
[0028] Preferably, the first sintering temperature is 300-700°C, for example, it can be 350°C, 400°C, 450°C, 500°C, 550°C, 600°C or 650°C, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0029] Preferably, the first sintering pressure is 1-10 GPa, for example, it can be 2 GPa, 3 GPa, 4 GPa, 5 GPa, 6 GPa, 7 GPa, 8 GPa or 9 GPa, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0030] Preferably, the first sintering time is 1-8h, for example, it can be 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h, 6h, 6.5h, 7h or 7.5h, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0031] In the present invention, the first sintering is performed at high temperature and high pressure to obtain a block-shaped sintered product, which is first crushed to obtain primary particles.
[0032] Preferably, the first crushing method includes ball milling, for example, wet ball milling, which further includes a drying step.
[0033] Preferably, the rotation speed of the first crushing is 500-5000rpm, for example, it can be 1000rpm, 1500rpm, 2000rpm, 2500rpm, 3000rpm, 3500rpm, 4000rpm or 4500rpm, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0034] Preferably, the first crushing time is 0.5-6h, for example, it can be 0.8h, 1h, 1.2h, 1.5h, 1.8h, 2h, 2.2h, 2.5h, 2.8h, 3h, 3.2h, 3.5h, 3.8h, 4h, 4.2h, 4.5h, 4.8h, 5h or 5.5h, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0035] Preferably, the average particle size of the primary particles is 0.1-50 μm, for example, it can be 0.2 μm, 0.5 μm, 1 μm, 2 μm, 5 μm, 8 μm, 10 μm, 12 μm, 15 μm, 18 μm, 20 μm, 22 μm, 25 μm, 28 μm, 30 μm, 35 μm, 40 μm or 45 μm, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0036] Preferably, the second sintering is performed in an inert atmosphere.
[0037] Preferably, the inert atmosphere includes a nitrogen atmosphere and / or an argon atmosphere.
[0038] Preferably, the temperature of the second sintering is 700-2000°C, for example, it can be 800°C, 900°C, 1000°C, 1100°C, 1200°C, 1300°C, 1400°C, 1500°C, 1600°C, 1700°C, 1800°C or 1900°C, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the said range.
[0039] Preferably, the second sintering time is 2-8h, for example, it can be 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h, 6h, 6.5h, 7h or 7.5h, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0040] As a preferred technical solution of the present invention, the first sintering is carried out at high temperature and high pressure, with a temperature of 300-700°C, a pressure of 1-10GPa, and a time of 1-8h; the second sintering is carried out at high temperature, with a temperature of 700-2000°C, and a time of 2-8h, and no additional pressure is required for the second sintering. By designing and optimizing the two sintering processes, the filling ratio of the modified boron nitride particles in the resin material can be further improved.
[0041] Preferably, the second crushing method includes ball milling, for example, wet ball milling, which further includes a drying step.
[0042] Preferably, the rotation speed of the second crushing is 500-5000rpm, for example, it can be 1000rpm, 1500rpm, 2000rpm, 2500rpm, 3000rpm, 3500rpm, 4000rpm or 4500rpm, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0043] Preferably, the second crushing time is 0.5-6h, for example, it can be 0.8h, 1h, 1.2h, 1.5h, 1.8h, 2h, 2.2h, 2.5h, 2.8h, 3h, 3.2h, 3.5h, 3.8h, 4h, 4.2h, 4.5h, 4.8h, 5h or 5.5h, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0044] Preferably, the resin material includes any one of epoxy resin, cyanate resin, polyphenylene ether resin, polybutadiene resin, butadiene-styrene resin, bismaleimide-triazine resin, bismaleimide resin, polytetrafluoroethylene resin, polyimide resin, phenolic resin, phenoxy resin, acrylic resin, liquid crystal resin, benzoxazine resin, and nitrile rubber, or a combination of at least two of them.
[0045] Preferably, the nitrile rubber includes any one of unmodified nitrile rubber, carboxyl-terminated nitrile rubber, and hydroxyl-terminated nitrile rubber, or a combination of at least two thereof.
[0046] Further preferably, the resin material includes any one of epoxy resin, polyphenylene ether resin, polybutadiene resin, styrene-butadiene resin, bismaleimide resin, phenolic resin, and phenoxy resin, or a combination of at least two thereof.
[0047] Preferably, the epoxy resin includes any one of bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin, novolac epoxy resin, biphenyl epoxy resin, phenol novolac epoxy resin, bisphenol A novolac epoxy resin, silicone-modified epoxy resin, phosphorus-containing epoxy resin, brominated epoxy resin, aliphatic epoxy resin, alicyclic epoxy resin, o-cresol epoxy resin, and dicyclopentadiene (DCPD) epoxy resin, or a combination of at least any two thereof.
[0048] Preferably, the polyphenylene ether resin is a polyphenylene ether having a terminal group containing a C=C unsaturated bond, and more preferably a polyphenylene ether having a terminal group containing any one or at least two of vinylbenzyl, vinylphenyl, acrylate, and methacrylate groups.
[0049] Preferably, the polybutadiene resin and the styrene-butadiene resin both contain cross-linkable active groups C=C, such as 1,2-vinyl based on butadiene monomers.
[0050] Preferably, the mass percentage of the resin material in the resin composition is 8-80%, for example, it can be 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70% or 75%, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range, and 9-50% is further preferred.
[0051] In a preferred technical solution, the resin composition comprises the following components in mass percentage: 4-50% epoxy resin (for example, 5%, 8%, 10%, 15%, 20%, 25%, 30%, 35%, 40% or 45%, etc.), 0-10% phenoloxy resin (for example, 0.1%, 0.3%, 0.5%, 0.8%, 1%, 2%, 4%, 5%, 6% or 8%, etc.), and 40-92% modified boron nitride particles (for example, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85% or 90%, etc.).
[0052] In another preferred technical solution, the resin composition comprises the following components in mass percentage: 4-50% hydrocarbon resin (e.g., 5%, 8%, 10%, 15%, 20%, 25%, 30%, 35%, 40% or 45%, etc.), 0-10% polyphenylene ether resin (e.g., 0.1%, 0.3%, 0.5%, 0.8%, 1%, 2%, 4%, 5%, 6% or 8%, etc.), and 40-92% modified boron nitride particles (e.g., 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85% or 90%, etc.).
[0053] In another preferred technical solution, the resin composition comprises the following components in mass percentage: 4-50% (e.g., 5%, 8%, 10%, 15%, 20%, 25%, 30%, 35%, 40% or 45%) of polyphenylene ether resin, 0-10% (e.g., 0.1%, 0.3%, 0.5%, 0.8%, 1%, 2%, 4%, 5%, 6% or 8%) of hydrocarbon resin, and 40-92% (e.g., 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85% or 90%) of modified boron nitride.
[0054] Wherein, the hydrocarbon resin includes polybutadiene resin and / or styrene-butadiene resin, preferably polybutadiene resin.
[0055] Preferably, the resin composition further comprises any one of a accelerator, an initiator, a cross-linking agent, a filler, a flame retardant, and a curing agent, or a combination of at least two thereof.
[0056] Preferably, the accelerator includes any one of imidazole compounds, organic complexes, tertiary amines, tertiary phosphines, and quaternary ammonium salts, or a combination of at least two thereof, and imidazole compounds are further preferred.
[0057] Preferably, the imidazole compound includes any one of 2-methylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-undecylimidazole, 1-benzyl-2-methylimidazole, 2-heptadecylimidazole, 2-isopropylimidazole, 2-phenyl-4-methylimidazole, 2-dodecylimidazole, and 1-cyanoethyl-2-methylimidazole, or a combination of at least two thereof.
[0058] Preferably, the mass percentage of the accelerator in the resin composition is ≤8%, for example, it can be 0, 0.1%, 0.3%, 0.5%, 0.8%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7% or 7.5%, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0059] Preferably, the initiator includes any one of an organic peroxide, an azo initiator, and a carbon-based initiator, or a combination of at least two of them.
[0060] Preferably, the organic peroxide includes any one of α,α'-di(tert-butylperoxy-m-isopropylbenzene)benzene, diisopropylbenzene peroxide, tert-butylperoxy-isopropylbenzene, bis(tert-butylperoxy-isopropyl)benzene, 1,1-bis(tert-hexylperoxide)-3,3,5-trimethylcyclohexane, 2,5-dimethyl-2,5-di(tert-butylperoxy)hex-3-yne, tert-butyl peroxyoctanoate, and tert-butyl peroxybenzoate, or a combination of at least two thereof.
[0061] Preferably, the initiator further comprises any one of triethylamine, triethylamine salt compounds, quaternary amine salt compounds, 2,4,6-tris(dimethylaminomethylamine)phenol, benzyldimethylamine, imidazoles, tripentylphenol amine, monophenol compounds, polyphenol compounds, boron trifluoride, boron trifluoride organic complexes, triphenyl phosphate, and triphenyl phosphite, or a combination of at least two thereof.
[0062] Preferably, the mass percentage of the initiator in the resin composition is ≤8%, for example, it can be 0, 0.1%, 0.3%, 0.5%, 0.8%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7% or 7.5%, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0063] Preferably, the crosslinking agent includes any one of triallyl isocyanurate, triallyl polyisocyanurate, triallyl cyanurate, trimethacrylic acid, diallyl phthalate, divinylbenzene, and multifunctional (meth)acrylate, or a combination of at least two thereof.
[0064] Preferably, the mass percentage of the crosslinking agent in the resin composition is ≤20%, for example, it can be 0, 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 8%, 10%, 12%, 14%, 15%, 16% or 18%, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0065] Preferably, the filler includes any one of silicon dioxide, titanium dioxide, barium titanate, strontium titanate, magnesium titanate, calcium titanate, barium strontium titanate, calcium barium titanate, lead titanate, lead zirconate titanate, lead lanthanum zirconate titanate, barium lanthanum titanate, barium zirconate titanate, hafnium dioxide, lead magnesium niobate, barium magnesium niobate, lithium niobate, potassium niobate, strontium aluminum tantalate, potassium tantalum niobate, barium strontium niobate, lead barium niobate, barium titanium niobate, strontium bismuth tantalate, bismuth titanate, barium rubidium titanate, copper titanate, and lead titanate-lead magnesium niobate, or a combination of at least two of them.
[0066] Preferably, the average particle size (D 50 The particle size) is 0.01-50 μm, for example, it can be 0.05 μm, 0.1 μm, 0.5 μm, 1 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, and specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively enumerates the specific point values included in the range. It is further preferred to be 0.01-30 μm, and even more preferred to be 0.01-10 μm.
[0067] Preferably, the mass percentage of filler in the resin composition is ≤20%, for example, it can be 0, 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 8%, 10%, 12%, 14%, 15%, 16% or 18%, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0068] A solvent may also be added to the above resin composition, and the amount of solvent added is selected by a person skilled in the art based on experience and process requirements, so that the resin composition reaches a viscosity suitable for use, so as to facilitate impregnation, coating, etc. of the resin composition. In the subsequent drying, semi-curing or complete curing stage, the solvent in the resin composition will partially or completely volatilize.
[0069] In another aspect, the present invention provides a resin adhesive, which comprises the resin composition as described in the first aspect and a solvent.
[0070] Illustratively, the solvent includes any one of a ketone solvent, an alcohol solvent, an aromatic hydrocarbon solvent, an ester solvent, and a nitrogen-containing solvent, or a combination of at least two thereof.
[0071] The solvent of the present invention is not particularly limited, and generally, ketones such as acetone, butanone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone, aromatic hydrocarbons such as toluene, xylene, and mesitylene, esters such as ethyl acetate, butyl acetate, and ethoxyethyl acetate, alcohols such as methanol, ethanol, and butanol, ethers such as ethyl cellosolve, butyl cellosolve, ethylene glycol methyl ether, diethylene glycol ethyl ether, diethylene glycol butyl ether, carbitol, and butyl carbitol, and nitrogen-containing solvents such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methyl-2-pyrrolidone can be used; the solvent can be used alone or in combination of two or more.
[0072] The resin composition provided by the present invention is prepared by the following method, which comprises: mixing and uniformly dispersing the components in the resin composition to obtain the resin composition.
[0073] In a second aspect, the present invention provides a prepreg, comprising a reinforcing material and the resin composition as described in the first aspect attached to the reinforcing material.
[0074] Preferably, the resin composition is attached to the reinforcing material by impregnation and then drying.
[0075] Preferably, the raw material of the reinforcing material includes any one of natural fibers, organic synthetic fibers, organic fabrics, and inorganic fibers, or a combination of at least two thereof; for example, glass fiber cloth, quartz glass fiber blended cloth, non-woven fabric, quartz cloth, fiber paper, and the like.
[0076] Illustratively, the method for preparing the prepreg is: using the resin glue of the resin composition to impregnate a reinforcing material, and then drying to obtain the prepreg.
[0077] Preferably, the drying temperature is 100-180°C, for example, it can be 110°C, 115°C, 120°C, 125°C, 130°C, 135°C, 140°C, 145°C, 150°C, 155°C, 160°C, 165°C, 170°C or 175°C, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range, and 115-175°C is further preferred.
[0078] Preferably, the drying time is 1-30 min, for example, it can be 2 min, 5 min, 8 min, 10 min, 15 min, 20 min or 25 min, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range, and 2-20 min is further preferred.
[0079] In a third aspect, the present invention provides a thermally conductive film, wherein the material of the thermally conductive film includes the resin composition as described in the first aspect.
[0080] Preferably, the thermally conductive film is obtained by coating the resin composition on a release material and then drying and / or semi-curing the resin composition.
[0081] In a fourth aspect, the present invention provides a metal foil-clad laminate, comprising a metal foil and at least one of the prepreg described in the second aspect and the thermally conductive film described in the third aspect.
[0082] Preferably, the metal foil in the metal foil-clad laminate includes any one of copper foil, aluminum foil, nickel foil, alloy foil, or a combination of at least two of them.
[0083] Preferably, the metal foil is copper foil, and the metal foil-clad laminate is a copper-clad laminate.
[0084] Preferably, the number of prepregs in the metal foil-clad laminate is 1-20, for example, 2, 3, 5, 7, 9, 10, 11, 13, 15, 17 or 19, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0085] Exemplarily, the method for preparing the metal foil-clad laminate comprises: laminating metal foil on one side or both sides of a prepreg and curing to obtain the metal foil-clad laminate; or, stacking at least two prepregs into a laminate, and then laminating metal foil on one side or both sides of the laminate and curing to obtain the metal foil-clad laminate.
[0086] Preferably, the curing is carried out in a press.
[0087] Preferably, the curing temperature is 170-280°C, for example 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, 260°C or 270°C, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0088] Preferably, the curing pressure is 1-10MPa, for example 1.5MPa, 2MPa, 3MPa, 4MPa, 5MPa, 6MPa, 7MPa, 8MPa or 9MPa, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0089] Preferably, the curing time is 30-300 min, for example 40 min, 50 min, 60 min, 80 min, 100 min, 120 min, 150 min, 180 min, 200 min, 220 min, 240 min, 260 min or 280 min, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0090] In a fifth aspect, the present invention provides a printed circuit board, comprising at least one of the prepreg described in the second aspect, the thermally conductive film described in the third aspect, and the metal foil-clad laminate described in the third aspect.
[0091] Compared with the prior art, the present invention has the following beneficial effects:
[0092] (1) In the resin composition provided by the present invention, boron nitride and a sintering aid of a specific type and amount are sintered and crushed twice. Through the special design of the preparation method, the modified boron nitride particles have a high filling rate in the resin material. The resin composition containing the modified boron nitride particles has high peel strength and excellent bonding properties while achieving high thermal conductivity, so that the metal foil-clad laminate achieves excellent comprehensive effects in terms of high thermal conductivity and high reliability.
[0093] (2) The present invention designs and optimizes the components and ratios of the resin composition so that the thermal conductivity of the copper-clad laminate containing the resin composition is ≥5.6 W / m·k and the peel strength is ≥0.8 N / mm, and the copper-clad laminate has excellent heat dissipation performance, interlayer bonding strength and reliability. DETAILED DESCRIPTION
[0094] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0095] The preparation method of the modified boron nitride particles is described below in conjunction with specific preparation examples, but the preparation method of the modified boron nitride particles is not limited to these preparation examples.
[0096] In the following preparation examples, boron nitride, sintering aids, and other metal oxides are all commercially available chemicals; among them, boron nitride has a lamellar structure and is purchased from 3M, CFP003.
[0097] Preparation Example 1-7
[0098] Modified boron nitride particles AG, the preparation method is as follows:
[0099] Boron nitride, sintering aids and optionally other metal oxides are weighed in parts by mass according to the ratio shown in Table 1, and physically dry mixed for 1 hour to obtain a mixture; the mixture is added to a grinding tool, and a first sintering is performed in a nitrogen atmosphere at the temperature, pressure and time shown in Table 1 to obtain a blocky first sintered product, which is wet-milled in a ball mill at a speed of 3000 rpm for 2 hours, and the particle size of the zirconium beads is 1-10 mm, and dried after ball milling to obtain primary particles; the primary particles are placed in a high-temperature furnace, and a second sintering is performed in a nitrogen atmosphere at the temperature and time shown in Table 1, and then the sintered product is placed in a ball mill for wet-milling at a speed of 3000 rpm for 1-5 hours, and the particle size of the zirconium beads is 1-10 mm; dried after ball milling to obtain modified boron nitride particles; the preparation of modified boron nitride particles with different particle sizes is achieved by controlling the second ball milling time.
[0100] Table 1
[0101]
[0102]
[0103] In Table 1, the units of the amounts of boron nitride (BN), sintering aids, and other metal oxides are "parts" (parts by mass), and "--" indicates that the component is not added. In Preparation Example 7, only the first sintering was performed, and the product obtained by the first sintering was crushed to obtain modified boron nitride particles G.
[0104] The average particle size of the modified boron nitride particles in Table 1 was tested by laser diffraction method, and the testing instrument was Malvern laser particle size analyzer, model MS3000.
[0105] The resin composition and application of the present invention will be described in detail below by taking a number of embodiments as examples, but the resin composition and application of the present invention are not limited to these embodiments.
[0106] In the following examples, the materials for which the preparation methods are not provided are all commercially available chemicals, and the specific information is shown in the following table:
[0107] category source Polybutadiene resin, B3000 Japanese Soda Polyphenylene ether resin, SA9000 Sabik Epoxy resin A, ZX1059 Nippon Steel Brominated Epoxy Resin, BEB531A80P Changchun, Taiwan, China Phenoloxy resin, YP-50EK35 Nippon Steel Initiator: 1,4-bis(tert-butylperoxyisopropyl)benzene (BIPB) Hunan Fangruida Chemical Co., Ltd. Accelerator: 2-methylimidazole (2-MI) BASF Modified Boron Nitride Granules AG Preparation Example 1-7
[0108] Examples 1-6, Comparative Examples 1-4
[0109] A resin composition, the types and amounts of the components are shown in Table 2, and the units of the amounts of the components are all "parts" (parts by mass).
[0110] A prepreg and a copper-clad laminate comprising the resin composition, the preparation method of which is as follows:
[0111] (1) mixing and evenly dispersing the components of the resin composition and the solvent (ethylene glycol methyl ether) according to the formula amount to prepare a glue solution with a solid content of 80%; impregnating the glue solution with a glass fiber cloth, placing the glass fiber cloth in an oven at 155° C. and baking it for 5 minutes to obtain a prepreg with a thickness of 5 mil;
[0112] (2) 6 prepregs are stacked, copper foils are stacked on both sides thereof, and the prepregs are laminated and cured in a hot press at 210° C. and 5 MPa pressure for 2 h to obtain the copper clad laminate.
[0113] The copper clad laminate is subjected to a performance test, and the specific method is as follows:
[0114] (1) Thermal conductivity: The thermal conductivity of the plate is tested according to the test method in standard ASTM-D5470;
[0115] (2) Peel strength: Refer to the test conditions in IPC-TM-650 2.4.8 method to test the peel strength of the sheet;
[0116] The performance test data is shown in Table 2.
[0117] Table 2
[0118]
[0119]
[0120] According to the performance test data in Table 2, the present invention mixes boron nitride with a sintering aid of a specific component and amount and then performs two sintering and crushing. Through the design of the preparation method, the modified boron nitride particles have a significantly improved filling rate. The modified boron nitride particles are compounded with a resin material so that the resin composition and the copper clad laminate prepared therefrom have high thermal conductivity and high peel strength. The thermal conductivity of Examples 1-4 is 5.6-15.7 W / m·k, and the peel strength is 0.8-1.49 N / mm, which has excellent comprehensive performance.
[0121] In Example 5, the amount of modified boron nitride particles used is relatively small, resulting in a decrease in the thermal conductivity of the copper clad laminate; in Example 6, the amount of modified boron nitride particles used is too large, resulting in poor processability of the composition and failure to prepare a qualified product.
[0122] According to the comparison between Example 2 and Comparative Examples 1-4, it can be seen that the sintering aid used in the modified boron nitride particles E in Comparative Example 1 is too little, and its modification effect is not obvious, resulting in that the modified boron nitride particles E still cannot achieve a high filling ratio, poor processability, and cannot produce qualified products. Unmodified boron nitride filler is used in Comparative Example 4, and high filling is also impossible, and qualified products cannot be produced. The modified boron nitride particles F in Comparative Example 2 use too much sintering aid, which affects the thermal conductivity of the material, resulting in a significant decrease in the thermal conductivity of the plate. The modified boron nitride particles G in Comparative Example 3 only undergo one sintering process during the preparation process, and its modification effect is insufficient compared to the two sintering processes of the present invention, resulting in a decrease in the thermal conductivity of the resin composition and copper clad laminate containing it.
[0123] The applicant declares that the present invention uses the above-mentioned embodiments to illustrate the resin composition, metal foil-clad laminate and its application, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A resin composition, characterized in that The resin composition comprises a combination of a resin material and modified boron nitride particles; The modified boron nitride particles are prepared by the following method, which includes: mixing boron nitride and a sintering aid, performing a first sintering and a first crushing to obtain primary particles; performing a second sintering and a second crushing on the primary particles to obtain the modified boron nitride particles; The sintering aid includes any one of calcium oxide, magnesium oxide, silicon oxide, yttrium oxide, niobium oxide, and potassium feldspar, or a combination of at least two thereof; based on the total mass of the boron nitride and the sintering aid being 100%, the mass of the sintering aid is 1-10%.
2. The resin composition according to claim 1, characterized in that The average particle size of the modified boron nitride particles is 0.1-30 μm; Preferably, the mass percentage of the modified boron nitride particles in the resin composition is 30-92%, more preferably 50-90%.
3. The resin composition according to claim 1 or 2, characterized in that The mixed raw materials also include other metal oxides; Preferably, the other metal oxides include aluminum oxide and / or beryllium oxide; Preferably, based on the total mass of the boron nitride, the sintering aid and the other metal oxides being 100%, the mass of the other metal oxides is 1-10%.
4. The resin composition according to any one of claims 1 to 3, characterized in that The first sintering is performed in an inert atmosphere; Preferably, the inert atmosphere comprises a nitrogen atmosphere and / or an argon atmosphere; Preferably, the temperature of the first sintering is 300-700°C; Preferably, the first sintering pressure is 1-10 GPa; Preferably, the first sintering time is 1-8h; Preferably, the second sintering is performed in an inert atmosphere; Preferably, the temperature of the second sintering is 700-2000°C; Preferably, the second sintering time is 2-8 hours.
5. The resin composition according to any one of claims 1 to 4, characterized in that The resin material includes any one of epoxy resin, cyanate resin, polyphenylene ether resin, polybutadiene resin, butadiene-styrene resin, bismaleimide-triazine resin, bismaleimide resin, polytetrafluoroethylene resin, polyimide resin, phenolic resin, phenoxy resin, acrylic resin, liquid crystal resin, benzoxazine resin, and nitrile rubber, or a combination of at least two thereof; Preferably, the mass percentage of the resin material in the resin composition is 8-80%, more preferably 9-50%.
6. The resin composition according to any one of claims 1 to 5, characterized in that The resin composition further comprises any one or a combination of at least two of an accelerator, an initiator, a cross-linking agent, a filler, a flame retardant, and a curing agent; Preferably, the accelerator comprises any one or a combination of at least two of imidazole compounds, organic complexes, tertiary amines, tertiary phosphines, and quaternary ammonium salts, and imidazole compounds are further preferred; Preferably, the imidazole compound includes any one of 2-methylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-undecylimidazole, 1-benzyl-2-methylimidazole, 2-heptadecylimidazole, 2-isopropylimidazole, 2-phenyl-4-methylimidazole, 2-dodecylimidazole, and 1-cyanoethyl-2-methylimidazole, or a combination of at least two thereof; Preferably, the mass percentage of the accelerator in the resin composition is ≤8%; Preferably, the initiator includes any one of an organic peroxide, an azo initiator, and a carbon-based initiator, or a combination of at least two thereof; Preferably, the organic peroxide includes any one of α,α'-di(tert-butylperoxy-m-isopropylbenzene)benzene, diisopropylbenzene peroxide, tert-butylperoxy-isopropylbenzene, bis(tert-butylperoxy-isopropyl)benzene, 1,1-bis(tert-hexylperoxide)-3,3,5-trimethylcyclohexane, 2,5-dimethyl-2,5-di(tert-butylperoxy)hex-3-yne, tert-butyl peroxyoctanoate, and tert-butyl peroxybenzoate, or a combination of at least two thereof; Preferably, the mass percentage of the initiator in the resin composition is ≤8%; Preferably, the crosslinking agent includes any one or a combination of at least two of triallyl isocyanurate, triallyl polyisocyanurate, triallyl cyanurate, trimethacrylic acid, diallyl phthalate, divinylbenzene, and multifunctional (meth)acrylate; Preferably, the mass percentage of the crosslinking agent in the resin composition is ≤20%; Preferably, the filler comprises any one of silicon dioxide, titanium dioxide, barium titanate, strontium titanate, magnesium titanate, calcium titanate, barium strontium titanate, calcium barium titanate, lead titanate, lead zirconate titanate, lead lanthanum zirconate titanate, barium lanthanum titanate, barium zirconate titanate, hafnium dioxide, lead magnesium niobate, barium magnesium niobate, lithium niobate, potassium niobate, strontium aluminum tantalate, potassium tantalum niobate, barium strontium niobate, lead barium niobate, barium titanium niobate, strontium bismuth tantalate, bismuth titanate, barium rubidium titanate, copper titanate, and lead titanate-lead magnesium niobate, or a combination of at least two thereof; Preferably, the mass percentage of filler in the resin composition is ≤20%.
7. A prepreg, characterized in that: The prepreg comprises a reinforcing material and a resin composition according to any one of claims 1 to 6 attached to the reinforcing material; Preferably, the resin composition is attached to the reinforcing material by impregnation and then drying.
8. A thermally conductive film, characterized in that: The material of the thermally conductive film comprises the resin composition according to any one of claims 1 to 6; Preferably, the thermally conductive film is obtained by coating the resin composition on a release material and then drying and / or semi-curing the resin composition.
9. A metal foil-clad laminate, characterized in that: The metal foil clad laminate comprises a metal foil and at least one of the prepreg according to claim 7 and the thermally conductive film according to claim 8 .
10. A printed circuit board, characterized in that: The printed circuit board comprises at least one of the prepreg according to claim 7, the thermally conductive film according to claim 8, and the metal foil-clad laminate according to claim 9.
Citation Information
Patent Citations
Method for preparing highly heat-conductive copper-clad plate
CN101767481A
High thermal conductivity copper clad plate and preparation method thereof
CN110370750A
Low-dielectric high-thermal-conductivity polytetrafluoroethylene high-frequency copper-clad plate and preparation method thereof
CN115556439A
Composite heat-conducting filler, resin composition, prepreg, circuit substrate and printed circuit board
CN117510994A
Boron nitride aggregated particle, aggregated bn particle-containing resin composition, and heat-radiation sheet
JP2015006980A